LES MENDZAN DES CHANTEURS DE YAOUNDE: Histoire - Organologie - Fabrication - Systeme de Transcription, by Pie-Claude Ngumu, No. 34, Acta Ethnoligica et Linguistica, Vienna, 1976„ pp. 81, photos, diagrams. - Gansemans, Jos (International Library of African Music, 1980)
pages: 132-133
Keywords: African Music